ARISTOTLE'S CONTRIBUTION TO THE DEVELOPMENT OF GOVERNMENT THEORY - Alexander V. Butov (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The article provides basic categories of the theory of government and analyzes advantages and disadvantages of different forms of state government offered by Aristotle. The author studies the evolution of developing legislation and systems of government of ancient Greece states - Sparta and Athens. The article also shows specific features of their legislative and executive bodies' functioning. Special attention is paid to the concept of Aristotle's ideal state and its benefits in comparison with models of state systems by Plato, Solon and Lycurgus. Research findings allow us to assess Aristotle's contribution to the development of theory and practice of government and to formulate new approaches to history of developing the government thought.